The Right to Communicate and Accessing Information on the Termination of Access Policy of Unregistered Private Scope Electronic System Operators - Rinalvin Achmad Wiryawan; Istislam Istislam; Dhia Al Uyun (International Journal Labs, 2024)
The policy of terminating access to Private Scope Electronic System Providers (Private Scope PSE), to several internet platforms including: Paypal, Yahoo, Epic Games, Steam, Dota, Counter Strike, Xandr.com, and Origin, which occurred on July 30, 2022. The termination of Private Scope PSE Access is due to the unregistered Private Scope PSE, whose provisions are regulated in the Permenkominfo PSE Private Scope. The policy of terminating access to the Private Scope PSE by the government is detrimental to citizens as users of the Private Scope PSE platform services whose access is terminated by the Government. Citizens have the right to communicate and access Private Scope PSE services which are Human Rights, as stipulated in the provisions of Article 28F of the 1945 Constitution of the Republic of Indonesia, Article 14 of the Human Rights Law, Article 19 of the Universal Declaration of Human Rights, and Article 19 of the International Covenant on Civil and Political Rights.